Impaired health-related quality of life in adolescents with allergy to staple foods. Issue 1 (December 2016) - Protudjer, Jennifer; Jansson, Sven-Arne; Middelveld, Roelinde; Östblom, Eva; Dahlén, Sven-Erik; Arnlind, Marianne; Bengtsson, Ulf; Kallström-Bengtsson, Ingrid; Marklund, Birgitta; Rentzos, Georgios; Sundqvist, Ann-Charlotte; Åkerström, Johanna; et al.
Abstract Background Cow's milk, hen's egg and wheat are staple foods in a typical western diet. Despite the ubiquity of these foods, the impact of staple food allergy on health-related quality of life (HRQL) amongst adolescents is incompletely understood. The aims of this study were to make use of the Swedish version of EuroPrevall's disease-specific food allergy quality of life questionnaire-teenager form (FAQLQ-TF) and to investigate the association between objectively-diagnosed staple food allergy and HRQL amongst adolescents. Methods In this cross-sectional study, 58 adolescents aged 13–17 years [n = 40 (69 %) boys] with objectively-diagnosed allergy to the staple foods cow's milk, hen's egg and/or wheat and living in Stockholm, Sweden were included. Adolescents completed the FAQLQ-TF, which has a corresponding scale of 1 = best HRQL, and 7 = worst HRQL. Overall HRQL and domain-specific HRQL were established. Adolescents also reported symptoms, adrenaline auto injector (AAI) prescription and presence of other food allergies. A history of anaphylaxis was defined among those reporting difficulty breathing, inability to stand/collapse, and/or loss of consciousness. Clinically different HRQL was set at a mean difference of ≥0.5. Results Overall mean HRQL was poorer than average [mean: 4.70/7.00 (95 % CI 4.30–5.01)]. The domain risk of accidental exposure was significantly associated with clinically better HRQL than the domain allergen avoidance and dietary restrictions (mean difference = 0.76; p < 0.001). Girls had clinically worse, but not statistically significantly different mean HRQL than boys (mean difference = 0.71; p < 0.07). HRQL tended to be worse amongst those with allergies to more than three foods or an AAI prescription. The number and types of symptoms, including a history of anaphylaxis were not associated with worse HRQL. Conclusions As ascertained via a food allergy-specific questionnaire, adolescents with staple food allergy report poorer than average HRQL, specifically in relation to emerging independence and the need for support. Girls have clinically worse HRQL than boys. The number and type of previous symptoms and history of anaphylaxis were not associated with worse HRQL.